К расчету свободномолекулярных полей течений - Басс, В.П.; Печерица, Л.Л. (Техническая механика, 2008)
Рассматриваются особенности численного моделирования газодинамических параметров в окрестности тел различной геометрической формы, обтекаемых сверхзвуковым потоком сильно разреженного газа. В качестве тестовой задачи выбрано обтекание диска, расположенного перпендикулярно набегающему потоку. Получены точные аналитические выражения для расчета концентрации молекул на оси симметрии диска, включая донную область. Features of numerical modeling of gas dynamical parameters are considered in a neighborhood of bodies of the various geometrical forms, which are flowed around by a supersonic stream of strongly rarefied gas. The flow around the disk located perpendicularly to running stream is chosen as a test problem. Exact analytical expressions for calculation of molecules concentration on a disk axis of symmetry including ground area are obtained.